Effects of simulated acid rain on in vitro pollen performance of Pyrus communis L. and Malus sylvestris Miller - Topdemir, Aykut; Gür, Nazmi (My University, 2011)
Successful fruit set depends on several reproductive processes including pollen germination and lube growth processes. Pollens of ( Pyrus communis I... and Mains sylvestris Miller flowers have been exposed 10 different concentrations of simulated acid rain solutions in range of pHs 6.0 to 2.8. Brawbaker Kwack medium was used for pollen germination. According to the results obtained, germination rate and pollen lube length for each plant at least has been affected at pH 6.0. Pollen germination and tube length significantly decreased with increasing acidity. The decrease of these rales for Malus sylvestris Miller was 99.44% for pollen germination and 99.68% for lube length: and for Pyrus communis 1... 96.23% for pollen germination and 96.75% for lube length at a pH of 2.8. lt has been shown that acidity has a higher effect on blocking Malus sylvestris Miller pollen performance in vitro comparative with Pyrus communis L.
Bildiri - Yayımlanmamış
Keywords: Acid rain; Apple; Pear; Pollen germination; Tube growth